ANALISIS PERBEDAAN MINAT BERWIRAUSAHA SEBELUM DAN SESUDAH MENEMPUH MATA KULIAH KEWIRAUSAHAAN PADA MAHASISWA STIE LAMPUNG TIMUR - Febriyanto - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
This study discusses the differences in student interest in entrepreneurship before and aftertaking entrepreneurship courses. The goal is to analyze the differences that arise with the provisionof entrepreneurship courses. Quantitative research methods used with this type of comparativestudy, research instruments using questionnaires given to students who have not been taking andafter taking entrepreneurship courses. The results obtained from this study is that there aredifferences in interest in entrepreneurship among students who already take entrepreneurshipcourses with that who have not taken yet. This difference provides opportunities for further researchto study about the most dominant interest in starting entrepreneurship.